2022
DOI: 10.18592/khazanah.v20i2.7944
|View full text |Cite
|
Sign up to set email alerts
|

Bright Students in Islamic Primary School From Low Income Family

Abstract: Learning is influenced by resources, context, and student input. High-achieving students who come from underprivileged families have supportive social capital to make up for the low financial and human capital in their families. The question addressed in this article is how to increase social capital in low-income families. This is a qualitative study. Data was collected by interviewing 63 informants, consisting of 28 parents and 35 high-achieving Islamic primary school (madrasah ibtidaiyah and madrasah tsanaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…The support is in the form of exceptional services to ethnic minorities, underprivileged students, and student groups facing academic problems. In line with the recommendations of Juhaidi et al, (2022) support to students is not only in the form of financial support (scholarships) or counseling on psychiatric problems (stress and depression) and careers but support that can fill the gap in their academic culture.…”
Section: Discussionmentioning
confidence: 75%
“…The support is in the form of exceptional services to ethnic minorities, underprivileged students, and student groups facing academic problems. In line with the recommendations of Juhaidi et al, (2022) support to students is not only in the form of financial support (scholarships) or counseling on psychiatric problems (stress and depression) and careers but support that can fill the gap in their academic culture.…”
Section: Discussionmentioning
confidence: 75%
“…In poor families, financial resources had no impact on the completion of education at the primary and secondary levels. They concluded that more financial support is needed in tertiary education [11]. Although parents are aware of the importance of their children's education, economic factors are the cause of the failure of Dayak Meratus children to achieve higher education [12].…”
Section: Introductionmentioning
confidence: 99%